2012
DOI: 10.1021/ja3055029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photophysical Properties of a Series of Cyclopenta[b]naphthalene Solvatochromic Fluorophores

Abstract: The synthesis and photophysical properties of a series of naphthalene-containing solvatochromic fluorophores are described within. These novel fluorophores are prepared using a microwave-assisted dehydrogenative Diels-Alder reaction of styrene, followed by a palladium-catalyzed cross coupling reaction to install an electron donating amine group. The new fluorophores are structurally related to Prodan. Photophysical properties of the new fluorophores were studied and intriguing solvatochromic behavior was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 26 publications
(32 reference statements)
1
92
0
1
Order By: Relevance
“…A MW-assisted intramolecular didehydrogenative Diels-Alder reaction of styrene-ynes (92) was reported to furnish fluorophores 93 (Scheme 2.66) [102,103]. (95) featuring close structural similarity to bioactive molecules were obtained by the intramolecular hetero Diels-Alder cycloaddition of alkyne triazines (94) under MW conditions in good yields (Scheme 2.67) [104].…”
Section: Diels-alder Cycloadditionsmentioning
confidence: 99%
“…A MW-assisted intramolecular didehydrogenative Diels-Alder reaction of styrene-ynes (92) was reported to furnish fluorophores 93 (Scheme 2.66) [102,103]. (95) featuring close structural similarity to bioactive molecules were obtained by the intramolecular hetero Diels-Alder cycloaddition of alkyne triazines (94) under MW conditions in good yields (Scheme 2.67) [104].…”
Section: Diels-alder Cycloadditionsmentioning
confidence: 99%
“…Donor groups including a pyrrolidyl 35, piperidine 37, morpholine 38, benzylamine 39, aniline 40, and paramethoxyaniline 41 were all installed via the Buchwald−Hartwig cross-coupling reaction, while different acceptor groups, such as aldehydes 36 and 42 and ester 43 were incorporated during synthesis of the IMDDA precursor. 27 Absorption and emission maxima along with quantum yields (not shown) for these dyes were measured in CH 2 Cl 2 ( Figure 1). The tertiary cyclic amino ketone series of compounds 35, 37, and 38 ranged in absorption maxima from 355 to 390 nm, with the pyrrolidylsubstituted dye 35 having the most red-shifted absorption maxima extending close to the visible region.…”
Section: Accounts Of Chemical Researchmentioning
confidence: 99%
“…It was found that isomers of Prodan with different positioning of the donor and acceptor group in the naphthalene core exhibit much stronger solvatochromic properties (Benedetti et al 2012). Its naphthalene core was also substituted with aromatic hydrocarbons possessing increased electronic conjugation.…”
Section: The Environment-sensitive (Solvatochromic) Dyesmentioning
confidence: 99%